HUBUNGAN PERAN KELUARGA SEBAGAI PMO (PENGAWAS MENELANOBAT) DENGAN KEJADIAN DROP OUT PADA PASIEN TBPARU DI POLI PARU RSUD SIDOARJO - Santoso, Windu; Maya Sari, Linda (Jurnal Keperawatan Bina Sehat, 2015)
Tuberculosis was known as TB is contaminant disease is caused by basil mycobacterium tuberculosis. The calculation of TB patient are increase from year because the spreading of TB is fast and easily. Unfortunately TB patient always disobey in using medicine. Therefore, they get drop out, the condition will fail for curing. In fact, the disease will spread more dangerous to others. PMO is a person who control and motivate the patient from drop out. In this case a family have a role for this curing. Because the psikological factor between the patient make the curing more easily. The research is analytic research with cross sectional. The role of family as PMO is independent variable and drop out is dependent variable. The research using consecutive sampling. The population in this research is using the family from TB patient as a new case in RSUD Sidoarjo. The sample in the research is 38 person. The analysis using spearman rho. The conclution from the research is there is a relationship between the role of family as PMO with drop out of TB, this variable refered p = 0,0000 (p < α 0,05). PMO should support the patient in using medicine, so it will prevent the patient from drop out.Keywords : Tuberculosis, Role, Drop O